Developing the ability to pronounce English by organizing International Phonetic Alphabet learning for grade 5 students - Charoensuk, Kamonphop; Prasertsang, Parichart (Journal of Green Learning, 2024)
This action research promotes English reading by organizing International Phonetic Alphabet or IPA learning for 5th grade students. The participants were eight students; the tools for data collection included IPA learning plans and reading aloud tests. We analyzed the data using descriptive statistics. In the first cycle, the ability to read and pronounce English received the highest score of 10 points, which is the total score. There were 8 students who did not pass the 70% criteria, accounting for 24.24% of the total number of students. The second cycle showed that the students passed the 70% criteria. It can conclude that IPA can improve students' English learning skills and foster their proficiency in handling foreign language. Teachers can employ this instructional method in their English class to encourage students to learn authentic phonetics as well.